تذکیر القرآن از مولانا وحید الدین خان میں مباحث دعوت: تجزیاتی مطالعہ: Analytical study of Dawah thoughts in Tazkir-ul-Quran - Muhammad Zafar Iqbal; Dr. Muhammad Sajjad (MEI, 2023)
Molana Waheed -ud-din Khan (1925) is a renowned Islamic scholar, preacher, Quranic commentator and thinker. He explained Islamic teachings according to contemporary needs and style. His writing and preaching style or method is very simple, effective and sweet. He focused on preaching and rectification in his scholarly work. He supposed that the massage of Islam is actually the massage of rectification and call of Islam. The Holy Quran is a book of Dawah and the mission of holy prophet is the mission of Dawah. Molana highlighted this thoughts in his research work. He named his Quranic commentary by Tazkir-ul-Quran, due to the fact that Quran is the book for call to Islam. Quranic teachings are natural. The historical events described in Quran are depends on well being of Humanity. Similarly, Quran describes the humanity and universe which has clear signs of right path for intellectalus. In Tazkir-ul-Quran, Molana has described the basic massage of Quran, which is welfare, rectification and call to Islam. The methodology, he adopted in commentary of a particular verse is the description of that verse about Quran and advise. In this article, dawah thoughts in Tazkir-ul-Quran are discussed. Basically, in this article. Sole selected verses from Tazkir-ul-Quran has been discussed to pin pont the Dawah thoughts of Molana Waheed.